Lithospheric Magnetic Anomalies According to the CHAMP Satellite Mission Data over the Western Himalayan Syntaxis and Surrounding Areas - Abramova, D. Yu; Abramova, L. M. (Izvestiya. Atmospheric and oceanic physics, 2023)
The spatial distribution of the lithospheric magnetic anomalies field obtained from German CHAMP satellite measurements for several years of its mission is investigated over the territory of the Indo-Asian collision, in particular, the Tarim region and the Western Himalayan syntax (WHS). Maps of the total intensity T a of the lithospheric magnetic field for these regions are given. The lithospheric magnetic anomalies field as a reflection of the consequences of the Indian lithospheric plate subduction under the Eurasian plate is discussed in the context of modern ideas about the geological and tectonic structure and geophysical processes of the region. The sign inversion of the magnetic anomalies over the northern part of the Indian Plate observed on T a maps is supposed as a result of the lower crust heating due to mantle processes, the rise of the Curie isotherm and, as a consequence, the loss of the initial magnetization of the lower crust. In order to study the WHS territory and its surroundings in detail, maps of the lithospheric magnetic anomalies field are constructed at the lowest level of CHAMP orbit as possible, which leads to an increase in their resolution by nearing the field sources. The relationship of detected regional anomalies with tectonic processes in this seismically active area and with other available geophysical information is discussed. An interpretation of the obtained information shows that the images of lithospheric magnetic anomalies distinctly correlate with modern view about the location of large-scale geological and tectonic structures.